The language of cultural ecopoetics : a linguistic articulation of ecological framing in The Arrival of Monsoon - Riaz, Shahida; Mahmood, Rasib; Habib, Akhter (Penerbit Universiti Kebangsaan Malaysia, 2022)
Eco-linguistics is a thriving research field which integrates the language-environment nexus in an interdisciplinary array of dimensions. Nevertheless, the linguistic analysis of ecopoetics in Pakistani context is an underexplored domain of inquiry. The present research scrutinises the linguistic pattern of literary environmental text, which employs the poetic register to deal with the subject of the human-nature interface, and the construction of ecocritical framing within its specific context. The poem, The Arrival of Monsoon (1985) by Taufiq Rafat, is selected as it fulfills Buell (1995)’s criteria of ‘Environmental Text’. The poem is analysed first in terms of processes and circumstances using Halliday’s model of transitivity analysis and then employing Arran Stibbe’s concept of ecological framing to unveil its system of meanings. The results demonstrate the foregrounding of material actions and events in the text. The selected poem’s text has an explicit emphasis on the existence and characteristics of Nature in comparison to human beings and this is achieved categorically with circumstances of location. These circumstances of location hold significant cultural images and thus help in assigning the text its ecosensitive stance while locating it within a specific cultural context i.e., Pakistan. The dualistic frame of Nature being both invigorating and dominating is manifested in the poem. The study will be significant to emerging writers, teachers and students who want to explore the themes of human-nature interaction in their writings.